City of Oxnard Statement Regarding the Ventura County Community College District's "2000 A.D. Educational Master Plan" and "Ten Year Facilities Plan" - Bob Brown:::::: (1973)
A presentation discussing the proposed Oxnard Community College and the plan presented in regards to the college.